UP Manila research manual. - University of the Philippines (Manila). University Research Council; University of the Philippines (Manila). Office of Research Services (Manila The Council, 1997)
A compilation relating to the research function of the University of the Philippines-Manila. Research organizational structure. National Institutes of Health. Research human resource development. Guidelines. Research facilities and services. Research management. It is created to supplement a prospective researcher with necessary information about basic and applied research.
Jointly published with the Office of Research Services, UP Manila.
Keywords: Research -- Philippines -- Handbooks, manuals, etc